Differential phenotypic and functional properties of liver-resident NK cells and mucosal ILC1s. (February 2016) - Tang, Ling; Peng, Hui; Zhou, Jing; Chen, Yongyan; Wei, Haiming; Sun, Rui; Yokoyama, Wayne M.; Tian, Zhigang
Abstract: Group 1 innate lymphoid cells (ILCs) consist of conventional natural killer (cNK) cells, tissue-resident NK cells and mucosal ILC1s. Recently identified liver-resident NK cells, which can mount contact hypersensitivity responses, and mucosal ILC1s that are involved in pathogenesis of colitis are distinct from cNK cells in several aspects, but the issue of how they are related to each other has not been clearly clarified. Here, we show that liver-resident NK cells and mucosal ILC1s have different phenotypes, as evidenced by distinct expression patterns of homing-associated molecules. Moreover, mucosal ILC1s exhibit tissue residency akin to liver-resident NK cells. Importantly, liver-resident NK cells express relative high levels of cytotoxic effector molecules, which are poorly expressed by mucosal ILC1s, and exhibit stronger cytotoxic activity compared with mucosal ILC1s. These results demonstrate differential phenotypic and functional characteristics of liver-resident NK cells and mucosal ILC1s, shedding new light on the diversity of ILC family. Highlights: Liver-resident NK cells and mucosal ILC1s express different homing receptors. Liver-resident NK cells and mucosal ILC1s developmentally require T-bet and NFIL3. Mucosal ILC1s are tissue-resident. Liver-resident NK cells but not mucosal ILC1s have strong cytotoxic function.